Exploring which test-taker characteristics predict young L2 learners' performance on listening and reading comprehension tests. (July 2021) - Sok, Sarah; Shin, Hye Won; Do, Juhyun
Test-taker characteristics (TTCs), or individual difference variables, are known to be a systematic source of variance in language test performance. Although previous research has documented the impact of a range of TTCs on second language (L2) learners' test performance, few of these studies have involved young learners. Given that young L2 learners undergo rapid maturational changes in their cognitive abilities, are susceptible to affective factors in unique ways, and have little autonomy with respect to the context of L2 acquisition, the relationship between their personal attributes and their test performance merit separate research attention. To fill this gap, we investigated the extent to which sixth-grade, Korean-L1, EFL learners' ( n = 107) TTCs predicted their performance on tests of L2 listening and reading comprehension. The TTCs under investigation included three cognitive characteristics (aptitude, phonological working memory, L1 competence), one affective factor (motivation), and two demographic variables (socioeconomic status and gender). Results showed that aptitude and phonological working memory significantly predicted participants' performance on both L2 listening and reading comprehension tests, whereas motivation predicted performance on the L2 listening comprehension test only. These findings suggest that higher aptitude, phonological working memory, and motivation contribute positively to young learners' L2 outcomes.